State of the art for articular cartilage morphological and composition imaging evaluation in football players - Tiago Lazzaretti Fernandes; João Paulo Cortez de SantAnna; Bruno Antônio Peres Fiorio; Rafaella Rogatto de Faria; André Pedrinelli; Marcelo Bordalo (Elsevier, 2022)
In this review, the authors discuss available MR imaging techniques for evaluating the morphologic and compositional characteristics of articular cartilage in clinical settings related to football players. Applications of each technique for monitoring and assessing cartilage injury in athletes and supervising the effects of treatments are discussed in detail. In addition, we've summarized studies that evaluated the presence of chondral lesions or their repair in football players.